PENGARUH TINGKAT PENGETAHUAN DAN PERSEPSI MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS ABULYATAMA TERHADAP PROGRAM VAKSINASI COVID-19 - Maliza, Maya; Elmiyati, Elmiyati; Riezky, Ade Kiky (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2023)
COVID-19 is a disease caused by the Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) virus. COVID-19 can cause several health problems such as fever, cough, shortness of breath, and acute respiratory syndrome. One of the ways that can be done to stop the spread of the COVID-19 virus is vaccination. In general, people cannot accept vaccination because they are worried about the safety and effectiveness of the vaccine. However, understanding and acceptance of the Covid-19 vaccine in Indonesia continues to increase. The purpose of this study was to determine the effect of the level of knowledge and perceptions of Medical Education study program students at the Faculty of Medicine, Abulyatama University on COVID-19 vaccination. This research is an analytic descriptive study with a cross sectional study design. The sample size of this study was 52 people who were taken by purposive sampling in April 2023. Data collection was done by distributing questionnaires via google from. The research data were analyzed using the Chi-Square statistical test. The results showed that as many as 98% of respondents' level of knowledge about COVID-19 vaccination was classified in the good category and had a good perception of the acceptance of COVID-19 vaccination. Keywords : Covid-19, Vaccination.